Avoiding Overcorrection to Increase Patient Satisfaction After Open Wedge High Tibial Osteotomy. Issue 9 (July 2022) - Lee, Sung-Sahn; Kim, Joo Hwan; Kim, Su; Jung, Eui Yub; Ryu, Dong Jin; Lee, Do Kyung; Wang, Joon Ho
Background: Achieving the postoperative mechanical axis passing through 62.5% of the tibial plateau is considered successful osteotomy surgery. Despite precise preoperative planning and surgical techniques, some procedures result in under- or overcorrection. Few studies have investigated the relationship between clinical outcomes and unintentional under- or overcorrection after open wedge high tibial osteotomy (OWHTO) using whole-leg standing radiographs. Purpose: To investigate the relationship between postoperative alignment using whole-leg standing radiographs and clinical outcomes after OWHTO. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 89 knees (72 patients) that underwent OWHTO between October 2013 and September 2018 were included. Patients with postoperative weightbearing line (WBL) ratios within 57% to 67% were classified as appropriate correction (group A; 45 cases), whereas ratios <57% and >67% were classified as undercorrection (group U; 20 cases) and overcorrection (group O; 24 cases), respectively. The following patient-reported outcomes (PROs) were investigated: International Knee Documentation Committee (IKDC) subjective score, Kujala score, and Knee injury and Osteoarthritis Outcome Score (KOOS). The correlation between postoperative WBL and PROs was analyzed. PROs were compared among the 3 groups. Results: Regarding the correlation between postoperative WBL ratio and PROs, a larger postoperative WBL ratio was significantly correlated with a poor IKDC subjective score ( P = .002), Kujala score ( P = .009), and KOOS. Group O showed inferior postoperative PRO scores when compared with group A or U, whereas group U showed a similar result to group A (mean IKDC subjective scores: group U, 62.0; group A, 61.2; group O, 47.6; P = .004). Conclusion: Overcorrection after OWHTO surgery correlated with inferior PROs; therefore, overcorrected alignment should be avoided for patient satisfaction. Knees with an undercorrected alignment showed clinical results similar to those with appropriate correction.